Kisah kisah al Qur'an: pelajaran dari orang orang dahulu - Shalah Abdul Fattah Al_Khalidy (Gema Insani Press, 2000)
Oen, Jil. 1=c.1; Jil.2=c.1; Jil.3=c.1-2/oen, jil.2=c.2/oen, jil.1=c.2/ast, jil.2 =c.3/jil.1 =c.3 jil.3 =c.3/why, .10-.13 (jl 2=c.3, jl.3=c.4-6)/nr,jil.1=c.4/nis,jil1=c.6